Douglas ebook - Burrowes, Grace (Lonely Lords, 2014)
Douglas Allen needs a home for his aching heart Douglas Allen, Viscount Amery, hates having arrived to his title without knowing how to manage his properties. Guinevere Hollister is a distant family connection raising her daughter in rural obscurity while stewarding the estate. Douglas reluctantly puts himself in Gwen's hands for lessons in land husbandry and discovers beneath her prickly exterior a woman of passion and honor. Yet despite the closeness they find, she will not marry him. Guinevere Hollister needs a champion When the powerful Duke of Moreland arranges an engagement between Gwen and his heir, Douglas knows the marriage is not what Gwen wants. In Douglas's eyes, Gwen deserves to make her own choices, and he will take on family, the meddling duke, and Gwen's own lonely, stubborn heart to ensure his lady's happiness. Another unforgettable Regency romance from award-winning, New York Times and USA Today bestselling author Grace Burrowes.